Pengaruh Ekstrak Tauge Dan Atonik Dalam Meningkatkan Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) - Insani, Mutiara; Nurcayani, Endang; Mahfut; Wahyuningsih, Sri (CV. Multi Kreasi Media, 2025)
Cayenne pepper (Capsicum frutescens L.) is a shrub plant of the Solanaceae family that is famous for its spicy taste and high demand in Indonesia. However, the growth of cayenne pepper plants requires optimal plant nutrients. One way to increase plant growth is through fertilization, either with organic fertilizer in the form of bean sprout extract (Vigna radiata L.) or the provision of Growth Regulators (ZPT) in the form of atonik. This study aims to determine the effect of bean sprout extract and atony on the growth of cayenne pepper, determine the most effective concentration of bean sprout extract and atony, and identify the interaction between the two. The research was conducted from February to April 2024 at the Botany Laboratory of FMIPA, University of Lampung, using a completely randomized design (CRD) with a factorial design. The first factor was the application of bean sprout extract with three concentrations (0%, 5%, and 10%), while the second factor was the application of atonic solution with two concentrations (0% and 10%). Each treatment was repeated five times, resulting in 30 experimental units. Parameters observed included plant height, root length, chlorophyll content, leaf visualization, fresh weight, dry weight, and relative water content. The data obtained were analyzed using Analysis of Variance (ANOVA) and Tukey's further test at the 5% level. The results showed that the application of 5% bean sprout extract and 0% atonik gave the best results in plant height, root length, and relative water content. The interaction between bean sprout extract and atony had an effect on the growth of cayenne pepper, but did not have a significant effect on chlorophyll content.